Long-term patient-reported outcomes and quality of life after tibiofemoral knee dislocations in patients with open growth plates: a retrospective case series from a Level 1 trauma center - Pierre Hepp; Yasmin Youssef; Ralf Henkelmann (European Journal of Trauma and Emergency Surgery, 2026)
Abstract Background Tibiofemoral dislocations in children and adolescents are rare, and treatment guidelines are primarily based on adult data and algorithms. This case series of four pediatric and adolescent patients aims to add to the limited literature and highlights key aspects of diagnosis, treatment, and patient-reported outcomes. Methods We conducted a retrospective-prospective single-center case series of pediatric and adolescent patients (< 18 years, open growth plates) treated for tibiofemoral knee dislocations at a Level 1 trauma center between 2017 and 2019. Clinical, radiographic, and intraoperative data were reviewed. In addition, long-term patient-reported outcomes covering both functional recovery and health-related quality of life were assessed using KOOS, IKDC, and EQ-55 D-L. Results Four patients (2 male, 2 female), aged between 12 and 16 years, were included in this case series. The mean follow-up was 7.3 years (range 6 to 8 years). All patients sustained Schenck Type III-L dislocations. Early MRI and vascular imaging identified frequent associated injuries such as meniscal and chondral lesions, avulsion fractures, in one case, peroneal nerve injury. A staged surgical approach was used in two of the four cases. No growth disturbances or deformities were observed in the patients based on the available clinical and radiological follow-up. Functional outcomes ranged from moderate to excellent (KOOS: 59–92%, IKDC: 62–100%), while EQ-5D-5L-derived TTO utility values ranged from 0.36 to 1.00, with persistent psychological distress reported by three patients despite good physical recovery. Conclusion Pediatric tibiofemoral dislocations can occur after both high- and low-energy trauma and require timely, individualized management. Staged reconstruction tailored to skeletal maturity appears safe and effective, yielding favorable functional outcomes without growth disturbances during long-term follow-up. However, favorable KOOS and IKDC scores did not uniformly correspond to equivalent health-related quality of life, and three of the four patients reported persistent psychological burden related to the injury. Routine psychosocial screening and support should therefore be integrated into the long-term follow-up of pediatric patients after severe knee injuries. Clinical trial number Not applicable.